Emergence of a localized total electron content enhancement during the severe geomagnetic storm of 8 September 2017 - Soto Beltrán, Carlos (2019)
In this work, the results of the analysis on total electron content (TEC) data before, during and after the geomagnetic storm of 8 September 2017 are reported. One of the responses to geomagnetic storms due to the southern vertical interplanetary magnetic field (Bz) is the enhancement of the electron density in the ionosphere. Vertical TEC (VTEC) from the Center for Orbit determination in Europe (CODE) along with a statistical method were used to identify positive and/or negative ionospheric storms in response to the geomagnetic storm of 8 September 2017. When analyzing the response to the storm of 8 September 2017 it was indeed possible to observe an enhancement of the equatorial ionization anomaly (EIA); however, what was unexpected was the identification of a local TEC enhancement (LTE) to the south of the EIA (∼40°S, right over New Zealand and extending towards the southeastern coast of Australia and also eastward towards the Pacific). This was a very transitory LTE that lasted approximately 4h, starting at ∼02:00UT on 8 September where its maximum VTEC increase was of 241.2%. Using the same statistical method, comparable LTEs in a similar category geomagnetic storm, the 2015 St. Patrick's Day storm, were looked for. However, for the aforementioned storm no LTEs were identified. As also indicated in a past recent study for a LTE detected during the 15 August 2015 geomagnetic storm, an association between the LTE and the excursion of Bz seen during the 8 September 2017 storm was observed as well. Furthermore, it is very likely that a direct impact of the super-fountain effect along with traveling ionospheric disturbances may be playing an important role in the production of this LTE. Finally, it is indicated that the 8 September 2017 LTE is the second one to be detected since the year 2016.